El movimiento estudiantil de La Plata en los tempranos sesenta (1955-1966): O la historia de una guerra fría también propia - Pis Diez, Nayla (Entre los libros de la buena memoria, 2022)
This book presents an investigation on the student movement of La Plata and the early processes of politicization that it experienced, in the period between 1955 and 1966.